Використання інструментів Deep Learning Toolbox - Яковенко, О. С. (ХНУРЕ, 2025)
The Deep Learning Toolbox in MATLAB provides a powerful set of tools for developing and training neural networks that can be effectively used for various signal processing tasks. This tool supports working with neural network types such as multilayer perceptrons (MLP), recurrent neural networks (RNN), LSTM (Long Short-Term Memory), and convolutional neural networks (CNN). All these architectures can be applied to analyze and process different types of signals, such as audio, images, time series, and biometric data.
Keywords: Deep Learning Toolbox; MATLAB